Chronic cough and its association with TB-HIV co-infection: factors affecting help-seeking behaviour in Harare, Zimbabwe - Mavhu, Webster (2010)
OBJECTIVE: To qualitatively investigate reasons why individuals who reported chronic cough of two weeks or more in a cross-sectional prevalence survey had not accessed community-based outreach or other diagnostic services. METHODS: This study was nested into a cluster randomised trial comparing two methods of providing community-level diagnosis for TB. Twenty individuals (12 males) with previously unreported chronic cough, due to undiagnosed pulmonary TB in 5 cases, were interviewed. An additional twenty individuals who had attended clinical services participated in two focus group discussions. Data were coded and analysed using grounded theory principles. RESULTS: Participants described cough, and specifically their own symptoms, as having many possible causes other than TB. People avoided care-seeking for cough in order to avoid a possible diagnosis of “TB2” (HIV-related TB). Waiting in the hope of spontaneous resolution was common. Delaying treatment-seeking was also a strategy for deferring costs. Another common theme was negative perceptions of health facilities, as places where people anticipated discourteous treatment and being put at risk of contracting TB and HIV. Expectations that they should be in control of their own health further contributed to delayed health-seeking in men. CONCLUSIONS: Some individuals remain reluctant to be investigated for chronic cough even when provided with community-level services, with fear of the connotations of being diagnosed with TB and an aversion to contact with health providers among the dominant themes. In men, deferred acceptance that a chronic cough should be investigated may be related to concepts of masculinity, especially when symptoms are mild.